PENGARUH PERILAKU KEPEMIMPINAN, KEMAMPUAN KOGNITIF, DAN KEPUASAN KERJA, TERHADAP KINERJA KARYAWAN - R. Soesetyo Soetadji (Jurnal Manajemen Pendidikan, 2011)
The objective of this research is to find out the effects of Leadership behavior, and employee’s Cognitive ability, on employee’s Job satisfaction and Performance, and direct effect of employee’s Job Satisfaction on employee’s Performance. The Yogyakarta Agency of Drug and Food Control (BPOM) permitted the research to be carried out at its Yogyakarta Branch (Balai Besar Pengawas Obat dan Makanan DIY), in 2010, with a sample size of 55 employees selected randomly out of total population of 112. Data obtained were analyzed by Path analysis, after the variables placed in a correlation matrix. The results showed that 1) Leadership behavior had both direct effect on employee’s Job satisfaction, and Performance, 2) Employee’s Cognitive ability had a direct effect on employee’s Performance, but had no effect on employee’s Job Satisfaction 3) Employee’s Job Satisfaction had no effect on employee’s Performance. The results of this research showed that Leadership behavior and Cognitive ability were the most important determinants that could be used to improve employee’s Job satisfaction, and Performance, through education and training program.